Physical activity level and factors associated with perceived stress among Peruvian university professors during the COVID-19 pandemic - Vera Ponce, Víctor Juan (2023)
Introduction: The COVID-19 pandemic led to the transition to remote work, triggering variations in stress and physical activity (PA), associated with context-specific instability. Objective: To identify the association between perceived stress (PS) and the level of physical activity (PA) and explore its relationship with the sociodemographic, family, work and individual characteristics of professors working remotely during the COVID-19 pandemic. Material and methods: Cross-sectional analytical study based on a virtual survey of professors. PS was assessed using the Perceived Stress Scale (PSS-14), and PA using an International Physical Activity Questionnaire. The prevalence of high PS and the association with PA were estimated using a Poisson regression analysis with robust variance that estimated crude prevalence ratios (cPR) and adjusted prevalence ratios (aPR) with a 95% confidence interval (CI). Five models were developed to assess associations of PS and PA with sociodemographic, family, work, and individual variables. Results: The information of 191 professors was analyzed; 39.27% were women, aged 52 (41–60). The prevalence of high stress was 47.12%. The age and being head of household did not show significant individual associations with PS. However, the regression analysis assessing the association of PS and other factors showed that compared to the moderate PA group, a statistically significant association was found between stress and high PA (aPR = 0.19; 0.06–0.59), low PA (aPR = 1.43; 1.02–2.01), mainly influenced by age, being head of household and sleep quality. Conclusion: Stress was associated with PA level, family and individual factors. These findings allow identifying characteristics, such as being head of household, age and quality of sleep among teachers, as being associated with a higher probability of having high stress.